Honeys from some different regions of Azerbaijan: bioactive characteristics based on phenolic profile and antioxidant activity. Issue 4 (7th August 2020) - Degirmenci, Atiye; Can, Zehra; Boyraci, Gulsum Merve; Yildiz, Oktay; Asadov, Elsevar; Kolayli, Sevgi
Abstract : Azerbaijan is an important region for the beekeeping and honey industry. Biochemical characteristics of eleven honey samples from different regions of Azerbaijan were analyzed through measuring electrical conductivity, optical activity, moisture content, proline and diastase number. Phenolic components are analyzed by reverse-phase high-performance liquid chromatography (RP-HPLC) with UV–Vis double beam detector. Sugars profiles of samples were carried out using HPLC with a refractive index detector (RID). Total phenolic content (TPC), ferric reducing antioxidant power (FRAP) and 2, 2-diphenyl-1-picryhydrazyl (DPPH) free radical scavenging activity were measured with the aim of gathering information on the antioxidant power of samples. Biochemical and antioxidant characteristics are also supported with melissopalynological data. Conductivity ranged between 0.32 and 0.82 mS cm −1, moisture 14.52 and 20.78%, proline 314.34 and 1077.21 mg kg −1, diastase 13.05 and 22.19. Azerbaijan honeys exhibited levorotatory properties. Total phenolic content varied from 18.82 to 154.75 mg gallic acid equivalent per 100 g honey. The results confirm that physico-chemical and biologically active properties of Azerbaijan honeys are affected by the flora and geographical variations.